2019
DOI: 10.1364/oe.27.031290
|View full text |Cite
|
Sign up to set email alerts
|

Bending and twisting effects on multicore fiber differential group delay

Abstract: In this paper we provide the theoretical and experimental evaluation of fiber bending and twisting effects on the group delay performance of a homogeneous 7-core fiber. We have experimentally evaluated the differential group delay between the central and outer cores for different curvature radii and twisting conditions, demonstrating that fiber twisting counteracts the degradation introduced by the curvature itself. These findings are generally applicable to time-sensitive application areas such as radio-over-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In this fashion, observing a maximum in one coincidence count group while observing all of the others near zero allows us to identify the relative phase values. The measurements in the X i bases were identified using the coincidence count signatures described above, while applying a controlled bending to the 4CF fiber at the output of the source, causing mechanical stress that changes the relative phases between cores [42]. The joint probability distributions obtained from the four X i measurements are shown in Fig.…”
Section: Entanglement Certificationmentioning
confidence: 99%
“…In this fashion, observing a maximum in one coincidence count group while observing all of the others near zero allows us to identify the relative phase values. The measurements in the X i bases were identified using the coincidence count signatures described above, while applying a controlled bending to the 4CF fiber at the output of the source, causing mechanical stress that changes the relative phases between cores [42]. The joint probability distributions obtained from the four X i measurements are shown in Fig.…”
Section: Entanglement Certificationmentioning
confidence: 99%
“…In fact, on actual deployed fiber scenarios the measured dynamic skew is in the order of picoseconds . Additionally, we see that each core skew behaves differently with the temperature, which could be caused by fiber bending and twisting and polarization mode dispersion …”
Section: Resultsmentioning
confidence: 86%
“…Finally, regarding bending and twisting effects on the true-time delay line performance, in we studied both theoretically and experimentally how bends and twists affect the core differential group delay on a 7-core MCF. There, we showed that, although fiber curvatures can produce high group delay skew between the fiber cores (especially on the outer cores), twist-induced perturbations help to diminish this effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations